Cellulosic Textile Fibers
By controlling the spinning bath composition and recycling components, the method enhances cellulose carbamate fiber strength and textile suitability, addressing the limitations of existing techniques and promoting sustainability.
Patent Information
- Application Number
- JP2024534572
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-07
- Filing Date
- 2023-01-05
- Publication Date
- 2025-01-24
AI Technical Summary
Existing methods for producing cellulose carbamate fibers fail to achieve sufficient strength and textile quality, particularly when using alkaline spinning techniques, and there is a need for a more sustainable and efficient method utilizing waste materials.
A method involving the dissolution of cellulose carbamate in an aqueous sodium hydroxide medium, spinning in an alkaline bath with controlled sodium hydroxide and sodium carbonate concentrations, and recycling a portion of the spinning bath to optimize fiber properties, including maintaining specific ranges of sodium hydroxide (1.0-1.99 wt%) and sodium carbonate (30 wt%) while adjusting spinning conditions to achieve optimal fiber formation.
The method produces cellulose carbamate fibers with improved tensile strength and elongation, suitable for textile applications, utilizing waste materials and reducing environmental impact through recycling and efficient use of sodium hydroxide.
Smart Images

Figure 2025501877000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing cellulose carbamate textile fibers, the cellulose carbamate textile fibers obtained by this method, their uses, and articles made with the cellulose carbamate textile fibers. [Background technology]
[0002] Cellulose, the most abundant renewable organic material on earth, exhibits excellent properties for textile applications. The viscose process remains the most widely used technique to produce regenerated cellulose fibres and films, despite environmental challenges. There is therefore a need to develop simpler, more sustainable fibres with improved properties compared to traditional production processes.
[0003] EP 1 470 162 A describes the preparation of cellulose carbamate from high-quality cellulose solutions. Cellulose carbamate is known as an environmentally friendly alternative for the production of man-made cellulose fibers.
[0004] EP 1509548 describes the production of fibers, films and other moldings from cellulose carbamate by direct dissolution in sodium hydroxide solution and spinning the solution into an acidic spin bath. WO 2021 / 038136 provided a method for pretreating cellulose for use in the formation of cellulose carbamate. The cellulose carbamate obtained from the carbamate process was dissolved for the production of cellulose carbamate fibers by a wet spinning process. Wet spinning of the cellulose carbamate dope was carried out using an acidic spin bath optimized for the cellulose carbamate process, for example containing sodium sulfate and free sulfuric acid.
[0005] GB 2164942 presents a process for dissolving and precipitating cellulose carbamate from an alkaline solution using a precipitant solution containing sodium carbonate. The spinning and precipitation solution also contains sodium hydroxide. WO 2018 / 169479 presents regenerated cellulose fibers spun from an aqueous alkaline spin dope. The method introduces a nanofiller additive to increase the strength of the cellulosic fibers. WO 2020 / 171767 also describes spinning a cellulose spin dope in an alkaline coagulation bath having a pH greater than 7.0.
[0006] Carbamate hydrolysis stops upon coagulation in acidic spin baths. When spinning in alkaline coagulation baths, cellulose regeneration gradually occurs during coagulation and tow drawing. However, although alkaline spinning techniques have been successful in forming bodies, they have not yet been able to produce fibers with sufficient strength properties or textile quality, for example.
[0007] Thus, despite many recent research and development projects in this field, there is still a need to provide further production methods that allow better utilisation of textile waste materials. Summary of the Invention
[0008] The object of the present invention is to overcome at least some of the problems associated with the prior art and provide man-made cellulose carbamate fibers of textile quality.In accordance with an embodiment, it has surprisingly been found that by modifying the spin bath and the conditions under which the fibers are drawn, man-made cellulose carbamate fibers with improved properties can be obtained.In particular, the method of the present invention allows the production of cellulose carbamate textile fibers at least in part from waste materials, and still allows the fibers to be obtained with sufficient strength for the textile industry.
[0009] The invention is defined by the features of the independent claims. Some particular embodiments are defined in the dependent claims.
[0010] According to one aspect, the present invention provides a method for producing a cellulose carbamate textile fiber, comprising the steps of: dissolving cellulose carbamate having a maximum nitrogen content of 2.5 wt% in an aqueous sodium hydroxide medium to form a cellulose carbamate dope containing zinc; spinning the cellulose carbamate dope in an alkaline aqueous spinning bath in a spinning unit to form filaments or filament tows, the temperature of the alkaline aqueous spinning bath being in the range of 35-60°C; and drawing the filaments or filament tows to obtain cellulose carbamate fibers; The method relates to a method in which the sodium hydroxide content of the spin bath is maintained within the range of 1.0-1.99 wt. %, the sodium carbonate content of the spin bath is maintained at a maximum of 30 wt. %, and a portion of the alkaline spin bath is withdrawn from the spinning unit for recycling.
[0011] According to a further aspect, the present invention relates to a cellulose carbamate textile fiber obtainable by this process, and also to the use of the cellulose carbamate textile fiber obtainable by this process in a yarn, a textile, a woven or knitted fabric, a textile garment or a nonwoven fabric.Furthermore, the present invention relates to a yarn, a textile, a woven or knitted fabric, a textile garment or a nonwoven fabric comprising the cellulose carbamate textile fiber obtainable by this process. [Brief description of the drawings]
[0012] [Figure 1] 2 illustrates a schematic diagram of a method according to an embodiment; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Man-made cellulose fibers are fibers whose structure and properties change during the manufacturing process. Man-made fibers are distinct from natural fibers such as silk, cotton, and wool. Man-made cellulose fibers are made from the same cellulose polymers that make up the structural fibers of cotton, hemp, flax, and wood. In man-made cellulose fibers, the cellulose is either obtained in a modified state, for example from the wood pulping process, or modified to regenerate into usable cellulosic fibers.
[0014] The cellulose carbamate textile fiber in the present invention refers to the fiber in the form of staple fiber, short cut fiber, flock, filament yarn, filament tow. The cellulose carbamate textile fiber in the present invention also refers to the fiber used in nonwoven applications. The term filament in this specification should be understood to include filament tow.
[0015] Linear density, a measure of the mass per unit length of a fiber, is used by textile manufacturers as a measure of fineness. Linear density in decitex (dtex) is the weight in grams of a 10,000m length of fiber. Decitex (dtex) is the recognized SI unit of linear density. Linear density (dtex) is measured according to ISO1973:2021.
[0016] Tensile strength is a measure of the strength of a fiber. It is usually defined as the ultimate (breaking) force of the fiber (in gram-force) divided by the linear density. Tensile strength is defined as the ratio of the ultimate (breaking) force / load to the linear density of the specimen. The tensile strength of a sample can be expressed in units such as cN / dtex, grams / tex, grams / denier, or Newtons / tex. Tensile strength of a fiber (cN / dtex) is measured according to ISO5079:2020.
[0017] In textile products, the term initial modulus is used to describe the initial resistance of a textile material to elongation and is measured using ISO5079:2020. In other words, it is a measure of the resistance of a fiber to a small initial elongation. The more the fiber resists stretching, the higher the modulus. The tangent of the angle that the initial curve makes with the horizontal axis is equal to the ratio of stress to strain. This ratio is called the initial modulus, but in textile science it is called the initial Young's modulus. The initial modulus of a textile material depends on the chemical structure, the degree of crystallinity, the orientation of the fibers, etc. The initial modulus is tan α = stress / strain.
[0018] Breaking elongation is the degree to which a fiber elongates due to a breaking force. Breaking elongation (%) = breaking elongation x 100 / original length of specimen. Measured according to ISO5079:2020.
[0019] The nitrogen content in cellulose carbamate textile fibers or cellulose carbamates refers to the amount of nitrogen chemically bound as carbamate groups in the cellulose. The nitrogen content (wt % based on the total weight) is measured according to SFS 5505:1988.
[0020] The average intrinsic viscosity in ml / g is determined by ISO5351:2010 (CED viscometry) and the average is the arithmetic mean. The content (wt%) of p-terephthalate and / or p-terephthalic acid and / or unhydrolyzed or partially unhydrolyzed polyester is determined by gas chromatography-mass spectrometry (GC-MS) as described in more detail in the experimental section (Examples 4 and 6).
[0021] In this specification, when weight percent (wt%) is used, it means weight percent within the relevant material, unless otherwise specified.
[0022] The feedstock can be various types of cellulose-rich textile waste, such as post-consumer waste, pre-consumer waste, industrial textile waste, or a by-stream from textile manufacturing. The textile waste can be collected and sorted. The terms recycled waste material and waste material can also be used interchangeably.
[0023] Unless otherwise specified, the term heat bath shall mean a bath containing a liquid having a temperature in the range of 75 degrees Celsius to 100 degrees Celsius.
[0024] According to a first aspect, the present invention provides a method for producing a cellulose carbamate textile fiber, comprising the steps of: dissolving cellulose carbamate having a maximum nitrogen content of 2.5 wt% in an aqueous sodium hydroxide medium to form a cellulose carbamate dope containing zinc; spinning the cellulose carbamate dope in a spinning unit into an alkaline aqueous spin bath to form filaments or filament tows, the temperature of the alkaline aqueous spin bath being in the range of 3560°C; and drawing the filaments or filament tows to obtain cellulose carbamate fibers; The method relates to a method in which the sodium hydroxide content of the spin bath is maintained within the range of 1.0-1.99 wt. %, the sodium carbonate content of the spin bath is maintained at a maximum of 30 wt. %, and a portion of the alkaline spin bath is withdrawn from the spinning unit for recycling.
[0025] By "spinning the cellulose carbamate dope in a spinning unit into an alkaline aqueous spin bath to form filaments or filament tows" it is meant that the cellulose carbamate coagulates and is formed into filaments while being extruded through a spinneret.
[0026] The method of the present invention is based on studies on the pretreatment of cellulose carbamate, dissolution in NaOH, and wet spinning of the same into textile fibers using an alkaline spin bath. It was observed that the spinning of carbamate fibers can be improved by varying the composition of the spin bath, thereby resulting in cellulose carbamate products with improved properties. Slow coagulation in an alkaline spin bath will not achieve the desired textile fiber properties, i.e. fibers, filaments or filament tows with linear density of 0.8-1.8 dtex, tensile strength and elongation of 2.0-2.9 cN / dtex, and optionally initial modulus of 50-120 cN / dtex. It is therefore important that coagulation occurs at an optimal rate.
[0027] To facilitate the coagulation of the fibres, the amount of sodium hydroxide is required to be at a low level. The part of the alkaline spin bath withdrawn from the spinning unit (having the composition of the spin bath at that time and place) contains sodium carbonate and less than 2 wt. % sodium hydroxide, preferably 1.5-1.99 wt. %, in particular 1.6-1.9 wt. % sodium hydroxide. The sodium carbonate content of the spin bath is maintained at a maximum of 30 wt. %.
[0028] In prior art solutions such as WO 2020 / 171767, the coagulation bath contains sodium hydroxide, and the numerical range given is only the preferred 3-10 wt% of sodium hydroxide. Examples of sodium hydroxide contents given are 5.3 and 5.6 wt%, i.e. significantly higher than in the present invention. The tensile strengths of the carbamate fibers obtained in this document were 16.9 and 18.9 cN / tex (Table 1), i.e. 1.69 and 1.89 cN / dtex. The tensile strength values obtained with the method of the present invention can lead to carbamate fibers having a tensile strength of at least 2.0 cN / dtex, or even at least 2.3 cN / dtex. Tensile strength is a measure of the strength of the fiber, and therefore the cellulose carbamate fibers of the present invention with high strength can be used with other fibers common in yarn and textile manufacturing, with at least 2.0 cN / dtex being considered an acceptable strength for textile fibers. This limit is not reached in the examples of WO 2020 / 171767. Furthermore, WO 2020 / 171767 teaches that as the NaOH concentration approaches about 2 wt% in the wash liquor, zinc typically begins to precipitate (in the form of zinc hydroxide), thus indicating to one skilled in the art that the amount of sodium hydroxide should not go all the way down to 2 wt%.
[0029] In the prior art solutions disclosed in WO 2018 / 169479, which relates not only to cellulose carbamates but also to regenerated cellulose fibers in general, the preferred spin bath is dilute sodium hydroxide (the concentration of sodium hydroxide is substantially lower than the sodium hydroxide concentration in the spin dope, given as 6-9%), and the spin bath is preferably kept at a temperature of about 10-40°C. Examples of cellulose used in the preparation of the spin dope herein include natural celluloses such as pulp, cotton, cotton linters, and regenerated cellulose obtained from cellulose solutions such as viscose or lyocell. The cellulose may be derivatized, for example carbamate. There are no examples in this document, nor are specific values for the sodium hydroxide concentration of the spin bath given. Only the wet tensile strength is given, but no examples of how it can be determined.
[0030] GB 2164942, whilst citing a maximum NaOH content of 3 wt%, also cites values as high as 5-6 wt% in the spin bath and in its examples uses 3 wt%, producing carbamate fibres with properties which the patentee considers to be fully satisfactory. The properties are not specified. Thus, in the prior art, the amount of sodium hydroxide in the spin bath is significantly higher.
[0031] In contrast to the prior art, in the method of the present invention, the spinning is optimized to cellulose carbamate in order to obtain optimal fiber properties, most importantly maximum strength of the resulting fibers. Thus, part of the zinc is dissolved in the spinning bath and recycled, while part of the zinc is removed from the spinning bath together with the fibers or filaments, with the aim of being washed later and recycled separately. Thus, the amount of zinc precipitated in the spinning bath is minimized. Furthermore, the temperature of the spinning bath, i.e., 35-60°C, is optimized to hasten the formation of fibers while increasing the solubility of zinc, even with a low sodium hydroxide content in the spinning bath. Thus, it has been confirmed that the combination of the selected sodium hydroxide content and the temperature of the spinning bath leads to improved results.
[0032] The preferred (1.5-1.99 wt%) or even more preferred (1.6-1.9 wt%) range of sodium hydroxide also minimizes zinc precipitation in the spin bath. A further advantage of using the preferred range of sodium hydroxide in the spin bath is that it is economically reasonable to recycle the spin bath even in such range. If the sodium hydroxide content of the spin bath is not maintained at a minimum of 1.0 wt%, the amount of spin bath that needs to be recycled, i.e., treated to reduce the amount of sodium hydroxide therein, would be too large for commercial use. In fact, recycling the spin bath involves various precipitation and evaporation steps that not only require initial investment in equipment, but also increase operating costs and energy demands. It is therefore important to ensure that no zinc remains in the spin bath.
[0033] Therefore, it is an essential feature of the present invention that the spin bath is recycled, and this recycling maintains the sodium hydroxide and sodium carbonate contents of the spin bath in the indicated range. In fact, since the cellulose carbamate dope is alkaline, sodium, especially sodium hydroxide, also enters the spin bath together with the cellulose carbamate dope, thereby increasing the sodium hydroxide content of the spin bath. Therefore, the amount of sodium hydroxide in the recycled spin bath (i.e., the spin bath with reduced sodium hydroxide content) that is returned to the spin bath must be lower than the desired amount of sodium hydroxide in the spin bath. Zinc is also recovered and recycled to the cellulose carbamate dope.
[0034] Since sodium hydroxide is added to the spin bath in the dope, the amounts of sodium hydroxide and sodium carbonate in the spin bath will vary from one location of the spin bath to another during use of the process. The amounts defined above are the arithmetic average of the amounts in the spin bath.
[0035] A portion of the spin bath can be removed from the spin bath at any suitable location, or at several different locations, such as from one or more points at the bottom of the spin bath or as an overflow of the spin bath. It is also possible to remove a portion of the spin bath from the spin bath (i.e., the vessel used for spinning) or from the recycle conduit(s).
[0036] In addition, the cellulose carbamate dope preferably has certain qualities, such as suitable viscosity. In fact, if the viscosity of the dope exceeds 15 Pas (at 20 degrees Celsius), the handling of the dope (pumping, filtering, removing air, etc.) becomes very difficult. Also, for optimal spinning, the cellulose carbamate concentration in the spinning dope needs to be sufficiently high, preferably at least 8.0 wt%. The viscosity of the cellulose carbamate dope increases due to impurities in the dope, non-uniform raw materials, and high molecular weight of the cellulose chains. Thus, according to an embodiment, the cellulose carbamate has a polydispersity index value (also called polydispersity) measured by a gel permeation chromatography (GPC) / size exclusion chromatography (SEC) device in the range of 2.0-5.0, preferably 2.0-4.0, more preferably 2.0-3.5, and an average intrinsic viscosity measured by CED viscosimetry according to ISO5351:2010 of 147-225 ml / g, preferably 161-197 ml / g. These properties are particularly important when using waste materials as in the preferred embodiment, because a high quality dope can be obtained by adjusting the properties of the cellulose carbamate. Thus, in order to obtain optimal properties in cellulose carbamate fibers, the viscosity of the spinning dope should be at most 15 Pas (at 20 degrees Celsius), which requires that the cellulose carbamate has the above polydispersity and intrinsic viscosity, i.e., a homogeneous and sufficiently narrow molecular weight distribution and a sufficiently small particle size.
[0037] The polydispersity index can be altered, for example, by adjusting the temperature, residence time and acid concentration in the acid treatment step, by adjusting the pH and ozone charge in the ozone bleaching and / or decolorizing step, by adjusting the hydrogen peroxide charge, pH and residence time in the hydrogen peroxide bleaching step, and / or by adjusting the pH and alkalinity, residence time, urea charge, carbamate temperature and pressure in the carbamate step.
[0038] According to an embodiment, the cellulose carbamate preferably comprises cellulose carbamate obtained from cellulose-containing waste materials in an amount of at least 25 wt% of the cellulose carbamate, more preferably at least 50 wt% of the cellulose carbamate, the waste materials being preferably selected from the group consisting of textile waste, paper waste, cardboard waste, agricultural waste and mixtures thereof. Waste materials refer to materials collected for recycling, such as used textile products, paper, cardboard, etc. Agricultural waste refers to various plant-based materials that cannot be used as food for humans or animals, such as crop residues, weeds, humus, sawdust, forest waste, etc. In addition, straw can also be used as a raw material.
[0039] According to a particular embodiment, the cellulose carbamate comprises cellulose carbamate obtained from textile waste, with the amount of cellulose carbamate being at least 50wt%, preferably at least 90wt% of cellulose carbamate.According to an embodiment, the raw material of the textile fiber is 100% textile waste, i.e. only textile waste is used as raw material.Therefore, the fiber of the present invention and its manufacturing method make it possible to manufacture textile fiber containing recycled material, and still have properties that allow it to be used in textile industry, such as weaving.
[0040] The cellulosic materials may include virgin cellulose and / or recycled cellulose from sources such as jute, hemp, kenaf, cotton, bagasse, etc. Man-made cellulose carbamate fibers according to embodiments have good resistance to abrasion, i.e., good strength properties. The fibers have an initial modulus similar to cotton, which allows the fibers of the embodiments described herein to provide good strength properties to threads, yarns, and fabrics made from combinations of virgin cellulose, e.g., cotton, intertwined with the fibers of the present invention.
[0041] In one embodiment, the cellulose carbamate textile fiber contains 90 wt% or more, especially 95 wt% or more, of cellulose by dry weight. Small amounts of non-cellulosic components such as plastics, nylon, polyethylene, polypropylene, elastane and possibly nitrogen-containing impurities such as biuret may also be present. In addition, spin finishes are used to improve processability, for example in carding and / or yarn manufacturing. Optionally, other additives can be incorporated into the cellulose carbamate textile fiber. Optional chemicals can be used to modify processability and / or to modify physical properties such as tensile strength, modulus or stretchability of the final product. Optional chemicals may act as tracers. Processing aids, surfactants, lubricants, wetting agents, stability, color and brightness adjusters, de-astringents such as titanium dioxide, for example anatase or rutile titanium dioxide, dyes, pigments, flame retardants, fillers, antistatic agents and adjuvants for reducing fiber friction may also be present in the cellulose carbamate textile fiber.
[0042] In a further embodiment, the cellulosic material comprises recycled waste material, suitably at least 50 wt%, preferably at least 75 wt% of the cellulose of said cellulosic material is formed by recycled textile waste. The man-made fibers can be combined with virgin cotton fibers or mechanically recycled cotton fibers, which can be intertwined to provide threads or yarns with interesting properties. Thus, for example, man-made fibers, optionally made from chemically recycled cotton, can be used to replace at least a portion of the virgin cotton in threads, yarns, textiles and other articles comprising cellulose carbamate fibers.
[0043] Indeed, according to an embodiment, at least 50 wt% of the raw material for the textile fibers is cellulose-containing waste, and at least 50 wt% of the cellulose-containing waste is textile waste. It is also possible to use at least 55, 60, 65, 70, 75, 80, 85, 90, 95 or 100 wt% of the cellulose-containing waste as raw material. Of this cellulose-containing waste, at least 50 wt% is textile waste, and the textile waste can be at least 55, 60, 65, 70, 75, 80, 85, 90, 95 or 100 wt% of the cellulose-containing waste. As will be described later, the cellulose-containing waste can also include, for example, paper and cardboard waste and polycotton blends.
[0044] The cellulose may be from a variety of sources and in the form of a variety of pulps, in one embodiment, the cellulose is selected from the group consisting of chemical pulp, mechanical pulp, thermomechanical pulp, chemi-thermomechanical pulp, and mixtures thereof. In further embodiments, the chemical pulp is selected from the group consisting of organic sorbent pulp, soda pulp, dissolving pulp, kraft pulp, sulfite pulp, hot water extracted pulp, and mixtures thereof. In embodiments, paper pulp is used. In further embodiments, dissolving grade pulp is used. Recycled pulp, such as deinked pulp, is also useful in embodiments. In certain embodiments, the cellulose is dry dissolving pulp.
[0045] The source of the raw material is either virgin form of chemical or dissolving pulp or recycled material such as recycled paper and / or cardboard containing chemical or dissolving pulp.
[0046] Natural plant fibers, in the form of chemical pulp or dissolving pulp, are useful as raw materials. The origin of natural plant fibers may be either in virgin form, natural plant fiber-containing textile products, or recycled natural fiber-containing textile products. Natural plant fibers include seed fibers such as cotton and kapok, bast fibers such as hemp, jute, kenaf, ramie, abaca, and linen, leaf fibers such as abaca, sisal, pineapple, and banana, and fruit fibers such as coir.
[0047] In one embodiment, the cellulose is obtained from recycled cellulose selected from the group consisting of paper, cardboard, cotton, cotton linters, wheat straw, rice straw, corn stover, hemp, kenaf, bagasse, bamboo, flax, jute, and mixtures thereof.Embodiments of the present method are particularly useful for pretreatment of such demanding pulps having multiple fibril layers, such as cotton, cotton linters, hemp, flex, linen, and other stem and seed fibers.
[0048] Likewise, virgin sources of cellulose are suitable as well. Thus, in embodiments, the cellulose is obtained from virgin cotton, virgin cotton linters, virgin wheat straw, virgin rice straw, virgin corn stover, virgin hemp, virgin kenaf, virgin bagasse, virgin bamboo, virgin flax, virgin jute, and mixtures thereof.
[0049] An embodiment relates to the manufacture of cellulose carbamate textile fibers. In one embodiment, the method includes the steps of pretreating a cellulosic material, cellulose carbamate formation to form cellulose carbamate, providing a cellulose carbamate dope by dissolving the cellulose carbamate in an aqueous alkaline medium to form a dope, spinning the cellulose carbamate dope by feeding the dope to a spinning unit that represents an aqueous spin bath, coagulating the cellulose carbamate from the dope to the aqueous alkaline spin bath to form cellulose carbamate filaments or filament tows, drawing the filaments or filament tows in one or more drawing units, optionally washing in one or more washing units, and optionally cutting to obtain cellulose carbamate fibers. The cellulose carbamate textile fibers produced by the method may be in the form of filaments or staple fibers.
[0050] Cellulose carbamate can be prepared by pretreating cellulosic material and subjecting the pretreated cellulosic material to cellulose carbamate. In an embodiment, the cellulosic textile material is pretreated by mechanically processing to a predetermined particle size, and the mechanically processed material is subjected to acid and alkali treatments in a cooking liquor, in a desired order, and optionally to bleaching or other decolorizing treatments. In an embodiment, the pretreatment of cellulose can include providing a mixture comprising cellulose and a liquor, and mechanically processing the mixture, for example by shear mixing in a continuous mechanical mixer. Such pretreatments are disclosed, for example, in WO 2021 / 181007.
[0051] The process of treating cellulose includes preparing a mixture having a solid content, said mixture comprising cellulose and a liquid, the mixture preferably having an initial solid content of at least 50% by weight of the mixture, preferably the initial solid content is more than 50% by weight of the mixture, for example 51% by weight of the mixture, 52% by weight of the mixture or more than 50% by weight of the mixture, such as 55% by weight of the mixture, preferably at least 65% by weight of the mixture, in particular up to 75% by weight of the mixture, most preferably up to 71% or 72% or 73% or 74% by weight of the mixture. Mechanical processing of such ultra-high consistency pulps as these improves the rearrangement of the lamellae of the fiber cell walls and improves the absorption of chemicals such as urea at the molecular level in the mixture or pulp, as compared to low consistency pulps. An initial solid content of at least 50 wt% of the mixture ensures efficient handling of the cellulose, i.e. sufficient shear forces are exerted on the cellulose walls to effectively break the cell walls and make the cellulose fibers accessible to solvents and chemicals. If the initial solids content is less than 50 wt%, for example less than about 45 wt%, the efficiency of cellulose processing decreases. Therefore, when adding urea, it is advantageous to have a solids content of 50-75 wt%. In an embodiment, it is preferred that the solids content does not exceed 90 wt% of the mixture, preferably the solids content does not exceed 75 wt% of the mixture. By maintaining a high consistency pulp with a solids content of not more than 90 wt% of the mixture, preferably not more than 75 wt% of the mixture, it is ensured that the cell wall structure does not close to absorb chemicals, since keratinization or recrystallization due to deactivation by loss of free hydroxyl groups does not occur.
[0052] Between the above limits, there is enough space for shear forces to act on the cellulose without tearing the fibrils from the cellulose surface, and the accessibility of the fibrils on the fiber cell walls to solvents and chemicals is increased, which is optimal. Mixtures with solids content at the above limits are optimal for cotton, for example, because the six-layer fibril structure is not soaked at such solids content. If cotton becomes soaked, the fibril structure will be locked, and it will be more difficult to break the fibril structure and increase the accessibility of the cellulose carbamate fibers.
[0053] Carbamate formation can be carried out, for example, as disclosed in FI Patent No. 112869, FI Patent No. 112795 and FI Patent Application Publication No. 20195717.
[0054] The carbamate group is stable under weakly alkaline conditions, neutral conditions and acidic conditions (e.g., alkaline spinning and drawing conditions). The carbamate group hydrolyzes under strong alkaline conditions (e.g., dissolved cellulose carbamate hydrolyzes in an alkaline aqueous solution having a NaOH content of at least, e.g., 6.5% by weight relative to the dope). The cellulose carbamate starts hydrolysis instantly after dissolving under alkaline conditions for producing the dope, and some carbamate groups hydrolyze during dissolution and degassing of the dope. The higher the temperature of the dope and the longer the time from dissolution to coagulation, the faster the rate of hydrolysis and the lower the amount of carbamate groups bound in the cellulose, i.e., the lower the nitrogen content bound in the cellulose. The rate of hydrolysis determines the degree of substitution of the cellulose carbamate. In an embodiment, the nitrogen content of the cellulose carbamate can be adjusted by changing the dissolving conditions, such as time, temperature and / or sodium hydroxide concentration. The nitrogen content for wet spinning of the cellulose carbamate is adjusted to produce textile quality fibers.
[0055] In some embodiments, the cellulose carbamate has an intrinsic viscosity of 147-225 ml / g, preferably 161-197 ml / g, based on CED viscosity measurement according to ISO 5351:2010. These intrinsic viscosities correspond to an average degree of polymerization (DP) of the cellulose carbamate of 181-290 and 200-250, respectively. In order to obtain a cellulose carbamate suitable for wet spinning of fibers, it is preferred to reduce the degree of polymerization of the cellulose carbamate from conventional values to the ranges of values described herein.
[0056] According to another embodiment, the nitrogen content of the cellulose carbamate is 0.52.0 wt%, preferably 0.81.5 wt%, based on the total weight of the cellulose carbamate, measured according to SFS5505:1988.
[0057] In one embodiment, the polydispersity (PD) of the cellulose carbamate is adjusted using an acid, such as a mineral acid or an organic acid, or a combination of acids. Sulfuric acid can be employed as the acid for adjusting the PD. It is beneficial for the optimum molecular weight distribution of the feedstock to include an acid treatment step in the preparation of the cellulose feedstock or to treat the feedstock with an acid before carbamate cellulose and urea, preferably before the alkaline treatment for at least partial hydrolysis of the polyester. The cellulose carbamate is obtained by reducing the polydispersity index from the conventional values of conventional cellulose carbamates (usually having a polydispersity index of 8 to 11) to values in the range of 2.0 to 5.0, preferably 2.0 to 4.0, most preferably 2.0 to 3.5, resulting in fibers with improved tensile strength. The use of cellulose carbamate polymers with a narrower molecular weight distribution (lower polydispersity index) coupled with a lower average intrinsic viscosity compared to materials containing a broader molecular weight distribution with a higher average intrinsic viscosity can result in spun fibers with improved yield strength and elongation. The dissolution of cellulose carbamate with optimal average degree of polymerization and optimal polydispersity is improved as a result of the cellulose carbamate dope. The nitrogen content of the cellulose carbamate can be modified, for example, by adjusting the pH and alkalinity, residence time, urea charge, carbamate temperature and / or carbamate pressure in the carbamate step.
[0058] After pretreatment and carbamate to provide cellulose carbamate, in an embodiment, the carbamate is dissolved in an aqueous alkaline medium to provide a cellulose carbamate dope. In one embodiment, the cellulose carbamate is dissolved in an alkaline aqueous solution containing sodium hydroxide and a zinc salt, preferably zinc oxide and / or zinc hydroxide. The addition of zinc has been shown to improve the solubility of the cellulose carbamate and improve the stability of the cellulose carbamate solution. The alkaline solution is made from sodium hydroxide and zinc oxide and / or zinc hydroxide, thereby forming a zincate salt. Thus, in an embodiment, the alkaline solution includes sodium zincate.
[0059] According to a specific embodiment, the cellulose carbamate dope comprises 8-11 wt%, preferably 8.510 wt%, cellulose carbamate, 5-8 wt% sodium hydroxide, and 0.08-1.6 wt%, preferably 0.08-1.2 wt% zinc. The dope may also comprise processing aids and / or other additives. The weight percentage (wt%) is calculated from the total weight of the cellulose carbamate dope. When zinc oxide (ZnO) is used, its amount is 0.1-2 wt%, preferably 0.1-1.5 wt%. It is also possible to use other zinc compounds, such as zinc hydroxide or a mixture of zinc oxide and hydroxide, for the preparation of sodium zincate. In fact, the cellulose carbamate may be dissolved in an alkaline aqueous solution containing sodium hydroxide and zinc oxide.
[0060] According to an embodiment, the dope has a viscosity of not more than 15 Pas (at 20 degrees Celsius), suitably in the range of 4-15 Pas, preferably 4-10 Pas, as measured by ASTM D1343-93:2019. These conditions, together with the spin bath, are considered to be the most optimal for the formation of good quality and strong textile fibers, since they ensure that the fibers or filaments are formed at a suitable speed and can then be stretched to a sufficient extent. Such fibers or filaments can therefore be drawn at a suitable draw ratio. In fact, it has been observed that the amount of cellulose carbamate in the dope is advantageously in the range of 8-11 wt %, since the resulting dry matter content is high enough for fast solidification of the fibers.
[0061] According to an embodiment, the sodium hydroxide content of the spin bath is maintained within the range of 1.0-1.99 wt%, preferably 1.5-1.9 wt%. According to another embodiment, the alkaline spin bath comprises sodium hydroxide and sodium carbonate in a weight ratio of 1:11 to 1:20. According to yet another embodiment, the sodium carbonate content of the spin bath is maintained within the range of 22-30 wt%, preferably 23-29 wt%, in particular 24-28 wt%. According to a preferred embodiment, the sodium hydroxide content of the spin bath is maintained within the range of 1.0-1.99 wt%, while the sodium carbonate content of the spin bath is maintained within the range of 22-30 wt%. According to another preferred embodiment, the sodium hydroxide content of the spin bath is maintained within the range of 1.5-1.9 wt% and the sodium carbonate content of the spin bath is maintained within the range of 23-29 wt%, or 24-28 wt%. The portion of the alkaline spin bath withdrawn from the spinning unit therefore has at least 22 wt. % sodium carbonate, preferably at least 23 wt. % and in particular at least 24 wt. % sodium carbonate. The alkaline spin bath therefore contains sodium carbonate in the range of 22-30 wt. %, preferably 23-29 wt. % and in particular 24-28 wt. %.
[0062] According to a further embodiment, to facilitate coagulation, the temperature of the alkaline spin bath is between 40 and 55° C., preferably between 45 and 50° C. These preferred temperatures of the spin bath have been observed to further speed up the formation of the fibers, while increasing the solubility of zinc, even though the sodium hydroxide content of the spin bath is low.
[0063] In this process, it is crucial that the composition of the spin bath is maintained within the predetermined values for sodium hydroxide and sodium carbonate and temperature. Furthermore, precipitated zinc particles are preferably removed from the spin bath, for example by filtration. Similarly, if sodium carbonate has crystallized, the crystals are removed. Furthermore, in order to keep the composition of the coagulation bath constant, carbon dioxide may be passed through the coagulation bath during the process. Carbon dioxide reacts with the free sodium hydroxide to form sodium carbonate.
[0064] Recycling to reduce the sodium hydroxide content of the removed portion of the spin bath may include removal of crystals and / or precipitates and / or impurities, which may be carried out as a separate step. The sodium hydroxide content of the removed portion of the spin bath is reduced by first partially removing the water and the crystallized sodium carbonate, e.g. by vacuum crystallization in combination with evaporation and lowering the temperature, and then diluting the concentrated sodium hydroxide containing zinc to the desired extent for reintroduction into the process.
[0065] After the recycling process, at least a portion of the recycled alkaline spin bath is preferably returned to the spinning unit. The sodium hydroxide content of the returned portion is preferably 0.2-1.9 wt%, i.e. lower than the maximum content of the spin bath. Preferably, a lower sodium hydroxide content is used, since sodium hydroxide enters the spin bath mainly in the (cellulose carbamate) spin dope. Similarly, the sodium carbonate content of the returned portion is preferably lower than 30 wt.%. The recycled alkali recovered from the spin bath can also be used to form the cellulose carbamate dope, or zinc can be removed separately from the recycled alkaline spin bath.
[0066] A portion of the recovered sodium hydroxide (preferably with a small amount of zinc remaining in dissolved form) can also be recycled to the cellulose carbamate dissolution. Thus, recycling can also include separating the sodium carbonate from the sodium hydroxide. All the different components of the spin bath can also be separated from each other and reused in the process, either in the dissolution unit or in the spinning unit.
[0067] According to an embodiment, after coagulation, the nitrogen content of the cellulose carbamate filaments is in the range of 0.40-1.0 wt %. Thus, because the cellulose carbamate is at least partially hydrolyzed prior to spinning, the carbamate in the fibers or filaments is at an adequate level and / or there is little need for post-treatment to reduce the nitrogen content of the fibers or filaments.
[0068] According to an embodiment, the spinning has a spinneret draw ratio in the range of 0.75 to 1.4, preferably 0.8 to 1.2. Furthermore, the total stretching after solidification of the filaments or filament tows may be at least 70% in length, preferably 90% in length or more, in particular 95% in length or more, or 70 to 120% in length, in the stretching unit. The stretching unit is preferably a hot liquid or liquid-containing bath. The alkaline liquid-containing bath in the stretching unit with a pH value above 7 may contain, for example, sodium hydroxide and sodium carbonate in an amount that is kept at a level of about 2 / 3 of the amount in the spinning bath.
[0069] In the spin bath, the cellulose carbamate is coagulated into cellulose carbamate filaments, preferably through one or more spinnerets having a plurality of holes. Such filaments can be recovered from the spin bath, subjected to drawing, optionally cut into fibers, and subjected to optional post-treatments in which the filaments or fibers are washed, bleached, and / or decolorized, and / or spin-finished. The spinnerets can have hole sizes of 45-60 μm, preferably 50-55 μm. The spinneret draw ratio (Dr) in alkali cellulose carbamate spinning is adjusted by the dope composition and spinning conditions so that the regeneration of cellulose is sufficiently fast. Spinning is carried out with a spinneret draw ratio in the range of 0.75-1.5, preferably 0.8-1.2.
[0070] For purposes of the embodiment, The draw ratio is the ratio of the take-up roller speed to the extrusion speed; The draw ratio is Dr=v, take-up / v, extrusion, where v is the velocity, ie, the velocity entering the spinneret and the velocity exiting the spinneret. Spinning diameter ratio (Dr)=π·a·b·ρ·α·φ 2 / (DTEX 1 (1+Ω / 100) 4 10 7 ) where a = 1.1150(1 + fiber moisture % / (100 + fiber moisture %)), so we expect the fiber moisture % to be 13.0%. b = 1.1350 (1 + % fiber shrinkage / 100), so we expect % fiber shrinkage = 13.5%. ρ = density of spinning dope at feed temperature (kg / m 3 ) α = cellulose carbamate content of spinning dope (wt%) φ=Spinneret hole diameter (m) DTEX = filament linear density (dtex) Ω = total godet extension (%) measured between the first and last godet.
[0071] The main purpose of drawing the filaments is to produce filaments with the desired strength by inducing sufficient orientation of the polymer molecules along the axial direction. A high degree of orientation of the cellulose molecules tends to increase the fiber's modulus and tensile strength. Thus, when the fibers are spun in an alkaline spin bath, the fiber properties (such as fiber morphology, molecular orientation, and fiber strength) can be manipulated during coagulation and drawing depending on the alkalinity, temperature, and residence time at each step. Further post-hydrolysis processing, such as washing and further post-treatment regeneration, can affect the nitrogen content of the finished fiber. The tows of cellulose carbamate filaments are drawn in the initial spin bath or immediately after the initial spin bath to improve the final initial modulus and tensile strength of the fiber. The fiber shape can be controlled by adjusting the degree of substitution of the cellulose carbamate participating in the spinning and drawing conditions, for example, rounded, oval, bean-shaped, or leaf-shaped fibers are obtained as a result of controlled spinning and drawing of the nitrogen-containing cellulose carbamate, forming a smooth surface.
[0072] In one embodiment, the dissolved cellulose is subjected to wet spinning while the filaments or filament tows are subjected to drawing in a drawing unit. In a particular embodiment, the drawing bath is a hot bath having a temperature of 75-100°C, preferably 85-95°C, more preferably about 90°C. The drawing bath can be the same bath as the spinning bath, but typically has a lower concentration of sodium hydroxide and sodium carbonate. For example, if the two baths are common, each part may be preferably partially divided and operated on a countercurrent principle. Thus, both the spinning bath and the drawing bath are containers, typically open at the top, but the drawing bath is typically covered with a lid and contains a hot liquid at a given temperature (or a narrow temperature range), and the fibers or filaments pass through the bath, immersed in the liquid, and typically under drawing.
[0073] The drawing unit may include one or more drawing baths, which typically contain sodium hydroxide and sodium carbonate in an amount about 2 / 3 of that in the spinning bath. Thus, the amount of sodium hydroxide in the drawing unit is about 0.66-1.32 wt% and the amount of sodium carbonate is less than 20 wt%, for example 14.5-19.9 wt%. An optimal salt concentration is maintained in the drawing bath to promote the formation of filaments or filament tows under drawing. The amount of sodium hydroxide and sodium carbonate in the (horizontal) drawing bath varies. Part of the more concentrated spinning bath composition drifts in the drawing bath with the fibers or filaments. The balance of the drawing bath is therefore maintained by water and / or circulating salt composition. The amount of sodium hydroxide and sodium carbonate returned to the drawing bath should be less than the desired amount of sodium hydroxide and sodium carbonate in the drawing bath circulation. The above stated amounts are the arithmetic average of the amounts in the drawing bath.
[0074] In a preferred embodiment, the filaments or tows of filaments are stretched in a stretching unit by at least 70% of their length, preferably by more than 90% of their length, in particular by more than 95% of their length, or by approximately 70-120% of their length, preferably by 90-120% of their length, in particular in a hot bath. Stretching by length means total stretching of the godet by adjusting the stretching stress of the filaments or tows of filaments between rotating rollers with different peripheral speeds, for example the peripheral speed of the first roller is 25 m / min and the peripheral speed of the last roller is 50 m / min, so that the stretching of the godet obtained is 100% of their length. Such a high level of stretching contributes to providing a product with a high initial modulus when the temperature of the stretching bath is between 75 and 100° C.
[0075] The carbamate groups are hydrolyzed in the alkaline bath. Thus, in an embodiment, the regeneration of carbamate cellulose occurs during coagulation, drawing and / or post-treatment, so that the fiber properties can be manipulated during regeneration, particularly using conditional drawing and / or conditional post-treatment. When spinning into an alkaline coagulation bath, the regeneration of cellulose occurs gradually during the coagulation and drawing of the tow, with the aim that the cellulose is regenerated to a sufficient degree already at the beginning of spinning to allow sufficient drawing.
[0076] In one embodiment, nitrogen removal can continue in the filament formation stage. Spinning parameters and drawing influence the fiber orientation, crystallinity and final shape of the fiber and therefore the mechanical properties of the fiber. In a further embodiment, the nitrogen content of the final product can be adjusted in the washing and post-treatment stages, where most of the remaining carbamate groups can be removed (hydrolyzed), especially in the alkaline washing step. In a preferred embodiment, the nitrogen content of the final product is in the range of 0.10-1.2 wt.%, preferably 0.15-1.0 wt.%, in particular 0.2-0.9 wt.%, by dry weight of the fiber. This corresponds to a degree of substitution (DS) of cellulose in the range of 0.012-0.144.
[0077] A low nitrogen content in the final product is beneficial when improved wet properties such as low wet elongation and high wet tensile strength are desired. In an embodiment, the nitrogen content in the final product ranges from 0.10 to 0.75 wt%, which corresponds to a degree of substitution of cellulose of 0.012 to 0.09.
[0078] Drawing under controlled process conditions allows tailoring the properties of cellulose carbamate fibers. The shape of the fiber cross section can be altered by drawing under controlled process conditions, for example, round / elliptical, bean-shaped, or leaf-shaped fiber cross sections can be obtained as a result of controlled drawing, creating a smooth surface with a cotton-like hand and feel.
[0079] For example, the fibers have a more homogeneous and smooth surface and internal structure, i.e. cross-section, compared to viscose fibers, which have an irregular sawtooth surface. The rounded structure of elliptical, bean or leaf-shaped fibers provides a high initial modulus.
[0080] The relative wet strength, i.e., tensile strength at break, of the fibers of the present invention is improved compared to viscose, which has a low tensile strength at break. In particular, the relative wet elongation of the cellulose carbamate fibers of the present invention is very good. In an embodiment, the cellulose carbamate textile fiber of the present invention has a wet elongation at break in the conditioned state of 85-110%, preferably less than 100%, for example 85-99.9%, especially 90-99.9% (wet / dry relative %) of the dry elongation at break, a wet strength of at least 0.9 cN / dtex, preferably 1.0 cN / dtex or more, and a relative wet strength of 40-80% (wet tensile strength / dry tensile strength), preferably 45-80%. (Relative means wet elongation at break wet elongation / dry elongation compared to a typical wet / dry elongation at break of about 120% for viscose).
[0081] The fibers or filaments may be washed (at least partially) prior to cutting to reduce the total salt content of the filaments or filament tows. The washing unit may include one or more washing baths, which typically contain amounts of sodium hydroxide and sodium carbonate that are about one-third the amount in the spinning bath and half the amount in the drawing unit. Thus, the amount of sodium hydroxide in the washing unit is about 0.33-0.66 wt% and the amount of sodium carbonate is less than 10 wt%, e.g., 7.3-9.9 wt%.
[0082] Sodium hydroxide and / or sodium carbonate, and zinc are preferably also recovered from the solutions of the stretching and washing units and recycled into the process. The process therefore preferably includes means for monitoring the pH and component amounts of the various baths, as well as means for withdrawing the solutions back into the units.
[0083] The method may optionally include one or more of the following process steps: a) an acid wash to remove zinc salt precipitation residues, b) a water wash, c) optionally a post-hydrolysis of the carbamate groups with hot alkaline liquor, d) an acidic and / or neutral and / or alkaline bleaching step and / or e) a spin finish. Steps a) and c) may be in either order, preferably with a water wash step between them. The carbamate groups are stable in acidic systems and are hydrolyzed in alkaline baths. One objective of such optional post-treatment may be to reduce the nitrogen content of the filaments to the range of 0.05-0.4 wt%.
[0084] In one example of post-hydrolysis, cellulose carbamate fibers having a nitrogen content of 0.8 wt.% and coagulated in an alkaline spin bath and stretched in an alkaline stretch bath were subjected to post-hydrolysis in a post-treatment by treating with a post-hydrolysis solution containing Na2CO3 and NaOH at 95°C for 3 minutes, and the nitrogen content of the recovered fibers was 0.17 wt.%.
[0085] In one embodiment, washing is carried out as a countercurrent wash using water or the effluent of a preceding or subsequent treatment step. In a preferred embodiment, the post-treatment device is operated on the countercurrent principle.
[0086] Zinc and its compounds can migrate from the dope to the spin bath and eventually dissolve from the fibers during post-processing. Zinc carbonate is slightly soluble in the spin bath and wash solutions and can therefore partially precipitate in the spin bath, while the majority migrates with the filaments to the draw bath and wash solutions where it also partially precipitates. Some of the zinc can remain in the filaments until any post-processing steps. If some of the zinc remains in the fibers or filaments after washing, an acid wash can be used, for example, to remove the zinc from the stabilized fibers by dissolving it in a suitable acid solution.
[0087] Finally, the resulting filaments or fibers are dried by known drying methods.
[0088] It has also surprisingly been found that the presence of cellulose carbamate fibers as described herein above can be determined by fluorescence detection. Thus, embodiments provide a method for determining the presence of cellulose carbamate fibers or articles comprising such fibers.
[0089] In an embodiment, the method comprises exposing an article to UV light, preferably 365 nm UV light, and detecting the fluorescence in the wavelength range of 400-520 nm caused by said cellulose carbamate fibers. In one embodiment, the article is a yarn, a tow of filaments, staple fiber, short cut fiber or flock. In a further embodiment, the article is a textile garment comprising such fibers, such as a bleached and / or colored article. In accordance with the above, in an embodiment, when cellulose carbamate is mixed with viscose, lyocell or modal in a fiber, filament, yarn or fabric, the presence of cellulose carbamate in the man-made cellulose carbamate fiber mixture can be detected by fluorescence, since other regenerated fibers do not fluoresce.
[0090] Fluorescence is the emission of light by a substance that has absorbed light or other electromagnetic radiation. The cellulose carbamate textile fibers according to the embodiments emit fluorescence. Typically, the emission by the fluorescent substance is long wavelength. The cellulose carbamate textile fibers according to the embodiments emit blue / turquoise light, for example, at wavelengths in the range of 450-490 nm, which can be visually observed when the fibers are exposed to UV light, particularly UV light at a wavelength of 365 nm. The fluorescence emission wavelength depends on the excitation wavelength. The fibers according to the embodiments fluoresce at wavelengths in the range of 420-520 nm (blue) when excited with UV light, particularly 365 nm, and fluoresce at wavelengths in the range of 600-750 nm (red) when excited with 546 nm.
[0091] Further embodiments relate to cellulose carbamate textile fibers obtained by the process embodiments, uses of fibers obtained by the process embodiments, and uses of cellulose carbamate textile fibers. Thus, an embodiment provides cellulose carbamate textile fibers obtained by the process embodiments described hereinabove. In an embodiment, the fiber has a p-terephthalate and / or p-terephthalic acid, and / or unhydrolyzed or partially unhydrolyzed polyester, in particular polyethylene terephthalate, content of 0.00005-0.5 wt %, determined by gas chromatography mass spectrometry, as described in more detail below in the examples. The amount may be, for example, less than 0.2 wt %, preferably less than 0.1 wt %. The presence of p-terephthalate and / or p-terephthalic acid, and / or unhydrolyzed or partially unhydrolyzed polyester indicates that textile waste material was used as a raw material in the production of cellulose carbamate.
[0092] According to yet another embodiment, the fiber has a linear density of 0.8-1.8 dtex, a tensile strength of 2.0-2.9 cN / dtex, and an initial modulus of 50-120 cN / dtex. In a preferred embodiment, the linear density is 1.1-1.5 dtex, the tensile strength of 2.1-2.8 cN / dtex, and the initial modulus of 70-120 cN / dtex. The measurement method is as described above. Fibers with dtex at the lower end of the range, such as 0.8-1.3, are suitable for providing e.g. lightweight textile products from fibers with a titer of typically about 1.5 or less. Cotton fibers typically have tensile strengths at and above the upper end of this range, while conventional wet-spun artificial cellulose carbamate fibers typically have tensile strengths at the lower end of this range. The cN / dtex values of artificial cellulose carbamate textile fibers according to the embodiment are measured in the dry, i.e. conditioned, state. The initial modulus values in the range of 50 to 120 cN / dtex are higher than those of conventional artificial viscose, which typically has a modulus measured in the dry state in the range of, for example, 20 to 40 cN / dtex.
[0093] In a further embodiment, the cellulose carbamate textile fibers of any of the above embodiments are used in yarns, textiles, woven fabrics, knits, textile garments, or nonwoven articles, such as textile tows, flocks, filament yarns, or filament tows.
[0094] Further embodiments relate to articles comprising cellulose carbamate textile fibers as described hereinabove. In one embodiment, a yarn comprises cellulose carbamate textile fibers as described above. In a further embodiment, a textile garment comprises cellulose carbamate textile fibers as described above. In a particular embodiment, a woven or knitted fabric comprises cellulose carbamate textile fibers as described above. In a preferred embodiment, a nonwoven article comprises cellulose carbamate textile fibers as described above. In a further embodiment, the cellulose carbamate fibers in the yarn, textile or fabric are combined with cotton fibers, in particular virgin cotton fibers. Thus, embodiments allow at least a portion of the cotton fibers, in particular virgin cotton fibers, to be replaced with man-made cellulose carbamate fibers, which can, for example, reduce the impact of the textile industry on the environment. The man-made cellulose carbamate fibers of the present embodiment have an initial modulus similar to that of cotton fibers, which allows cotton to be replaced by said man-made fibers.
[0095] Detailed Description of the Drawings FIG. 1 shows a schematic representation of a method according to an embodiment. Cellulose carbamate 1 is fed to a dissolving unit 2. In this embodiment, the amount of cellulose carbamate is 8-11 wt%, sodium hydroxide 5-7 wt% and zinc 0.16-1.2 wt%, the remainder being water. The dissolved cellulose carbamate in the form of a cellulose carbamate spinning dope from the dissolving unit is led to a spinning bath 3 by extrusion through a spinneret(s). In the spinning bath, the amount of sodium hydroxide is maintained in the range of 1.0-1.99 wt%, and the amount of sodium carbonate (Na2CO3) is maintained in the range of 22-30 wt%. The spun filaments or fibers are then passed to one or more drawing units 4. In the drawing units, the amount of sodium hydroxide and sodium carbonate is maintained at a level of about 2 / 3 of the amount in the spinning bath. The stretching unit may include one unit or multiple units, and in the case of multiple units, they may be completely separate or partially connected to each other.
[0096] Here, the amount of sodium hydroxide and sodium carbonate is kept at a level of about 1 / 3 of that in the spin bath. After washing, the fibers or filaments are cut in a cutting unit 6 and optionally post-treated in one or more post-treatment units 7, 8, 9 and 10. The first optional post-treatment unit 7 is an alkaline washing unit, in which nitrogen is hydrolyzed. The second post-treatment unit 8 is a washing unit in which the cut fibers or filaments are washed with water. The third optional post-treatment unit 9 is an acid washing unit, the purpose of which is to dissolve the zinc using sulfuric acid. The alkaline washing unit may contain Na2CO3 and NaOH. The fourth optional post-treatment unit 10 is an alkaline bleaching step using hydrogen peroxide. The fifth post-treatment unit 11 is a spin finishing unit. Typically, the post-treatment units 8 and 11 are always used, while the post-treatment units 7, 9 and 10 are more optional and vary, for example, depending on the conditions of the upstream process and / or the intended use of the material. After drying in a drying unit 12, the cellulose carbamate fibers 13 are recovered.
[0097] The figure further shows several recycling routes for the process. Indeed, sodium hydroxide and sodium carbonate (both indicated with reference 17) are led from the spin bath 3 to the separation unit(s) 14 and, if necessary, are returned to the spin bath. Similarly, sodium hydroxide and sodium carbonate (both indicated with reference 18) are withdrawn from the stretching unit(s) 4 and led to the separation unit(s) 14. These compounds can also be withdrawn, if necessary, from other units downstream of the stretching units, although this is considered significantly less necessary.
[0098] The separation unit can also separate zinc 16 from the incoming stream and recycle it to the dissolution unit 2. Additionally, sodium hydroxide and / or sodium carbonate can be directed to a pretreatment unit 15, or to carbamate formation, if desired.
[0099] Working Example Example 1. Chemical pretreatment and carbamate formation Recycled mixed colour sorted cotton textile waste, polycotton raw material with a CED viscosity of 800ml / g (ISO5351:2010) containing 4.0wt% non-fibres (mainly polyester but also traces of nylon, isoprene-containing materials (elastic bands), polyethylene / polypropylene), was mechanically shredded and the fabric structure disrupted to form shreds with fibres of average fibre length 6mm. The shredded material was chemically pre-treated using a two-stage cooking procedure and bleaching / decolourisation: in the first acid stage the material was treated with sulphuric acid; in the second alkaline stage the washed acid treated material was chemically treated with sodium hydroxide to hydrolyse most of the polyester.
[0100] In the first acid stage, the shredded material was treated with sulfuric acid at 95 degrees Celsius for 60 minutes. The consistency of the textile waste was 10 wt% and the initial acid charge was 5.0 g / L. The medium consistency pulp was treated in a continuous plug flow reactor. The pH value of the final wash was 3.2, measured in the wash filtrate, which corresponds to 0.6 g free sulfuric acid per kg dry acid. The viscosity of the acid was 294 ml / g (based on CED viscosity measurement according to ISO 5351:2010).
[0101] In the second alkaline stage, the washed acid treated material was chemically treated with sodium hydroxide at 110°C for 120 min in a pressure reactor equipped with a medium consistency pump. The textile waste concentration was 8.3 wt% and the initial alkaline charge was 72 g / L. The pH value of the final wash liquor was 10.0. The viscosity of the chemically pretreated material was 290 ml / g (based on CED viscosity measurement according to ISO 5351:2010). The average yield in the alkaline stage was 92 wt% solids on oven-dried material.
[0102] The degree of polymerization was further adjusted in the bleaching stage, which included both ozone and alkaline hydrogen peroxide treatment steps. Ozone treatment in the alkaline range does not significantly reduce the CED viscosity of the material. In particular, the loss in viscosity is less than that obtained with ozone under acidic conditions. Thus, the narrow polydispersity index obtained in the preceding process steps is maintained in the alkaline bleaching stage. The raw material obtained in the bleaching process was appropriately dehydrated in a press and air stream for the subsequent carbamate process.
[0103] Ozone decolorization was carried out using a medium consistency loop and a pressure reactor. The loop was first filled with warm soft water and chopped fibre (300 kg, bone dry) was transferred to the system. The feedstock and water slurry was then fed into the pressure reactor. NaOH, 20 kg / BDT (bone dry metric ton of feedstock) was fed into the reactor to give a pH of 11.8 and a textile waste concentration of 8.5 wt%. The pretreated textile water slurry was heated to 70°C. The ozone concentration fed to the reaction was estimated to be 16 wt% and the feed time was 150 min. The total ozone charge was 4.0 kg / BDT. After the ozone stage, the slurry was replenished with 4.0 m 3 The mixture was cooled by adding water. The cooled and diluted slurry was dewatered in a screw press. The pH of the filtrate was 10.0. The viscosity after ozone decolorization was 279 ml / g (ISO5351:2010).
[0104] Next, the peroxide stage was carried out on the ozone decolorized textile material. The ozone treated material was pumped to the reactor and the concentration of the slurry in the pressure reactor was 8.0 wt%. The reaction mixture was heated to a reaction temperature of 80°C and the pH was adjusted to 11.6 with NaOH. The reaction time in the peroxide stage was 60 min and the hydrogen peroxide charge was 5 kg / BDT. The decolorized material was thoroughly washed in a screw press. The consistency of the screw press feed was 2.2 wt% and the thickening factor was 21 in the first washing sequence. In the second washing, the thickening factor was 25 times. The viscosity of the resulting decolorized pulp was 265 ml / g (ISO5351:2010).
[0105] The carbamate process was carried out as described in FI Patent No. 112869, FI Patent No. 112795 and WO 2021 / 038136. During the carbamate stage, the degree of polymerization of cellulose and the polydispersity of the final product were optimized by chemicals, time, grinding and time. After carbamate of the decolorized sample (mentioned above), the viscosity of the obtained cellulose carbamate was 210 ml / g (ISO5351:2010), with a DP of 268 and a PD of 3.28.
[0106] Example 2. Wet spinning of cellulose carbamate dope in an alkaline spin bath The cellulose carbamate obtained in Example 1 (samples 1-5 and comparative samples 1 and 2) was further dissolved and cellulose carbamate fibers were produced by a wet spinning process. That is, the ground air-dried cellulose carbamate powder was slurried and dissolved in 6.5 wt% sodium hydroxide and 1.2 wt% sodium zincate (zinc oxane) aqueous solution. The target cellulose carbamate content in the dope was 7.3-8.5 wt%. Sample 6 was prepared from cellulose carbamate obtained by the same manufacturing process. The viscosity of the cellulose carbamate used in sample 6 was 195 ml / g (ISO5351:2010), the degree of polymerization (DP) was 247, and the polydispersity (PD) was 3.41. The cellulose carbamate dope obtained from the dissolution process was then filtered using a two-stage backflush filtration process using a 20 μm filter medium in the second filtration stage.
[0107] Wet spinning of the filtered and degassed cellulose carbamate dope was carried out using an alkaline spin bath optimized for the cellulose carbamate process, containing 22.1-27.6 wt% sodium carbonate and 1.2-2.8 wt% sodium hydroxide. The cellulose dope was coagulated in a spin bath (temperature 45 °C) and subjected to a total godet stretching stress of 60-115% under a hot bath (temperature 90 °C). The spun filament tow was cut into staple fibers with a cut length of 40 mm. Fiber linear density (dtex), fiber tensile strength (cN / dtex), elongation (%) and initial modulus (cN / dtex) were measured according to ISO1973:2021 and ISO5079:2020. The dried fibers were conditioned for at least 24 h at a relative humidity of 65 ± 2% and a temperature of 20 ± 2 °C. The test speed was 20 mm / min, the gauge length was 20 mm, and the average value was 20 measurements (Favigraph, Textechno). The dope properties, spinning conditions, drawing conditions, and measured stable fiber properties are summarized in Table 1, where NR stands for no results.
[0108] [Table 1]
[0109] Example 3. Recycling of alkaline spin bath 912 L / h of equilibrium spin bath was withdrawn from the spin unit and contained 1.69 wt% sodium hydroxide, 22.1 wt% sodium carbonate and 0.13 wt% zinc. 40 L / h of spin dope containing 8.5 wt% cellulose carbamate, 6.5 wt% sodium hydroxide and 0.62 wt% zinc was continuously extruded into the spin bath to form and recover fiber filaments. The majority of the spent spin bath, 762 L / h, containing the above amounts of sodium hydroxide, sodium carbonate and zinc, was circulated back to the spin unit without recovery or manipulation. The remaining solution was withdrawn from the spin unit for recycling in order to reduce the sodium hydroxide content in the spin bath. 138 L / h of the recycled spin bath was returned to the spin unit. The returned portion of the recycled alkaline spin bath contained 0.43 wt% sodium hydroxide and 28.1 wt% sodium carbonate. Most of the recycled sodium hydroxide, along with the recycled soluble zinc compound, was returned to the cellulose carbamate dissolution stage to form the spin dope.
[0110] Example 4. Determination of terephthalic acid content The content of terephthalic acid in the cellulose carbamate fiber produced by the method described in Example 1 was measured by a GC / MS (gas chromatography-mass spectrometry) system. The sample was acidified with hydrochloric acid to pH<3 and dried in an oven overnight. Free terephthalic acid was extracted from the sample with pyridine / methanol solvent and concentrated to 5 ml. The extracted terephthalic acid was methylated and analyzed by GC / MS. The free terephthalic acid content in the sample was calculated against an external calibration standard. The amount of terephthalic acid was 10 mg / kg (dry cellulose carbamate fiber).
[0111] Example 5. Determination of terephthalic acid content The content of terephthalic acid in the cellulose carbamate fiber (cut length 40 mm) produced as described in Example 2 was measured by a GC / MS (gas chromatography-mass spectrometry) system. The sample was first refluxed in sodium hydroxide (10 wt%) for 4 hours to hydrolyze the polyethylene terephthalate in the sample. The terephthalic acid was extracted from the sample, dissolved in pyridine / methanol solvent, and concentrated to 5 ml. The extracted terephthalic acid was methylated and analyzed by GC / MS. The terephthalic acid content was calculated against an external calibration standard. The amount of terephthalic acid was 85 mg / kg (dry cellulose carbamate fiber).
[0112] It is to be understood that the disclosed embodiments of the invention are not limited to the particular structures, process steps, or materials disclosed herein, but extend to equivalents thereof that would be recognized by one of ordinary skill in the relevant arts. It is also to be understood that the terminology used herein is used for the purpose of describing particular embodiments only, and is not intended to be limiting.
[0113] Throughout this specification, a reference to an embodiment or an embodiment means that a particular feature, structure, or characteristic described in connection with the embodiment is included in at least one embodiment of the present invention. Thus, although the phrases "in one embodiment" or "in an embodiment" appear in various places throughout this specification, they do not necessarily all refer to the same embodiment. For example, when a numerical value is referred to using terms such as about, substantially, etc., the exact numerical value is also disclosed.
[0114] As used herein, a plurality of items, structural elements, components, and / or materials may be presented in a common list for convenience. However, these lists should be construed as if each member of the list were individually identified as a separate and unique member. Thus, the individual members of such lists should not be construed as de facto equivalents of other members of the same list solely based on their presentation in a common group, absent a contrary indication. Furthermore, various embodiments and examples of the invention may be referred to herein along with alternatives of its various components. It is understood that such embodiments, examples, and alternatives are not construed as de facto equivalents of each other, but are considered as separate and autonomous representations of the invention.
[0115] Furthermore, the described features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, numerous specific details are provided, such as examples of lengths, widths, shapes, etc., to provide a thorough understanding of embodiments of the invention. However, one of ordinary skill in the relevant art will recognize that the invention can be practiced without one or more of the specific details, or with other methods, components, materials, etc. In other instances, well-known structures, materials, or operations are not shown or described in detail to avoid obscuring aspects of the invention.
[0116] While the above-described examples illustrate the principles of the present invention in one or more particular applications, it will be apparent to those skilled in the art that numerous changes in form, use and details of implementation may be made without the exercise of inventive faculty and without departing from the principles and concepts of the present invention. Accordingly, it is not intended that the present invention be limited except as by the scope of the claims which follow.
[0117] In this specification, the verbs "comprise" and "include" are used as open-ended limitations that do not exclude or require the presence of any unrecited features. Features recited in the dependent claims may be freely combined with each other, unless otherwise expressly stated. Furthermore, it is to be understood that the use of "a" or "an", i.e., the singular form, throughout this specification does not exclude the plural form.
Claims
1. 1. A method for producing a cellulose carbamate textile fiber, comprising: Dissolving cellulose carbamate having a maximum nitrogen content of 2.5 wt % in an aqueous sodium hydroxide medium to form a cellulose carbamate dope containing zinc; spinning the cellulose carbamate dope in a spinning unit into an alkaline aqueous spin bath to form filaments or filament tows, the temperature of the alkaline aqueous spin bath being in the range of 35-60°C; and drawing the filaments or filament tows to obtain cellulose carbamate fibers; A process in which the sodium hydroxide content of the spin bath is maintained within the range of 1.0-1.99 wt %, the sodium carbonate content of the spin bath is maintained at most 30 wt %, and a portion of the alkaline spin bath is withdrawn from the spinning unit for recycling.
2. 2. The method of claim 1, wherein the cellulose carbamate comprises cellulose carbamate obtained from a cellulose-containing waste material, preferably in an amount of at least 25 wt. % of the cellulose carbamate, more preferably at least 50 wt. % of the cellulose carbamate, the waste material preferably being selected from the group consisting of textile waste, paper waste, cardboard waste, agricultural waste and mixtures thereof.
3. 3. The method of claim 1 or 2, wherein the cellulose carbamate comprises cellulose carbamate obtained from textile waste in an amount of at least 50 wt% of the cellulose carbamate, preferably at least 90 wt% of the cellulose carbamate.
4. The method according to any one of claims 1 to 3, wherein the nitrogen content of the cellulose carbamate is from 0.5 to 2.0 wt%, preferably from 0.8 to 1.5 wt%.
5. The method according to any one of claims 1 to 4, wherein the cellulose carbamate has a polydispersity in the range of 2.0 to 5.0, preferably 2.0 to 4.0, more preferably 2.0 to 3.5, measured by a Gel Permeation Chromatography / Size Exclusion Chromatography apparatus, and an average intrinsic viscosity in the range of 147 to 225 ml / g, preferably 161 to 197 ml / g, measured by CED viscometry according to ISO 5351:2010.
6. The method according to any one of claims 1 to 5, wherein the cellulose carbamate is prepared by pretreating a cellulosic material and subjecting the pretreated cellulosic material to cellulose carbamate formation.
7. 7. The method of claim 6, wherein the pretreatment comprises a mechanical treatment to obtain a cellulosic material of a predetermined particle size, followed by an acid and alkali treatment in a cooking liquor, and optionally a bleaching and / or decolorizing treatment.
8. 8. The method of any one of claims 1 to 7, wherein the cellulose carbamate dope comprises 8 to 11 wt%, preferably 8.5 to 10 wt%, cellulose carbamate, 5 to 8 wt% sodium hydroxide, and 0.08 to 1.2 wt% zinc, the dope having a viscosity of less than or equal to 15 Pas (measured at 20 degrees Celsius), suitably in the range of 4 to 15 Pas, as measured by ASTM D1343-93:2019.
9. A method according to any one of the preceding claims, wherein the sodium hydroxide content of the spin bath is maintained in the range of 1.0 to 1.99 wt%, preferably 1.5 to 1.9 wt%.
10. The method according to any one of claims 1 to 9, wherein the alkaline spin bath comprises sodium hydroxide and sodium carbonate in a weight ratio of 1:11 to 1:
20.
11. The method according to any one of the preceding claims, wherein the sodium carbonate content of the spin bath is maintained in the range of 22-30 wt.%, preferably 23-29 wt.%, in particular 24-28 wt.%.
12. The method according to any one of the preceding claims, wherein the temperature of the alkaline spin bath is in the range of 40 to 55°C, preferably 45 to 50°C.
13. The method according to any one of the preceding claims, wherein the spinning has a spinneret draw ratio in the range of 0.75 to 1.4, preferably 0.8 to 1.
2.
14. 14. The method according to claim 1, wherein the total drawing after solidification of the filaments or filament tows in the drawing unit, in particular in the hot bath, is at least 70% in length, preferably 90% in length or more, in particular 95% in length or more, or 70-120% in length.
15. 15. The method of any one of claims 1 to 14, further comprising at least one post-treatment step selected from an acid treatment to remove zinc oxide residues from the filaments and a post-hydrolysis treatment to reduce the nitrogen content of the filaments to the range of 0.05 to 0.4 wt %.
16. The method according to any one of claims 1 to 15, wherein the nitrogen content of the cellulose carbamate filaments after coagulation is in the range of 0.40 to 1.9 wt%.
17. A cellulose carbamate textile fiber obtainable by the method according to any one of claims 1 to 16.
18. 18. The cellulose carbamate textile fiber of claim 17, having a p-terephthalate and / or p-terephthalic acid, and / or unhydrolyzed or partially unhydrolyzed polyester content of 0.00005 to 0.5 wt % as determined by gas chromatography-mass spectrometry.
19. A cellulose carbamate textile fiber having a linear density of 0.8 to 1.8 dtex, a tensile strength and elongation of 2.0 to 2.9 cN / dtex, and an initial modulus of elasticity of 50 to 120 cN / dtex, preferably a linear density of 1.1 to 1.5 dtex, a tensile strength and elongation of 2.1 to 2.8 cN / dtex, and an initial modulus of elasticity of 70 to 120 cN / dtex.
20. Use of the cellulose carbamate textile fibre obtained by the process according to any one of claims 1 to 16 in yarns, textiles, woven or knitted fabrics, textile garments or nonwoven fabrics.
21. A yarn, textile, woven or knitted fabric, textile garment or nonwoven article comprising cellulose carbamate textile fiber obtainable by the process of any one of claims 1 to 16.